PENERAPAN METODE INFERENSI FORWARD CHAINING DALAM MENDIAGNOSA PENYAKIT KULIT PADA KUCING - Saryoko, Andi; Putri, Yustin Anggraheni (Jurnal Pilar Nusa Mandiri, 2016)
Among of many animals, Cat is one of the most favorable domestic animal in our society too keep pets in a good health, the cat owner should pay attention by feeding a good and take care the cat so the cat is not going to be susfeptible disease. Skin disease is one of a type of disease that mostly infect pets, especially cats.cat owner sometime realize that the pet is often become less such as ballnes, smell, and skin redness to the cat yet many cat owner are not seacrhed the veterinaly care of treatement, because because their busy at work also cost for mediacation is too expensive for several cat owner who have small income. The veterinary clinic usually pleaced in towns, so the cat owner who lived in the villange is not able to bring ther pet to animal care (clinics). One of the alternativethat could be used by the cat owner to salve the problem is using a disgnostic expert systm in the website (Web) based in Forward Chainning. This system diagnosis skin in cats is usefull to provide information to pevent skin disease and analize the characteristic featunes to skin that injured disease.